BISPHOSPHONATE-RELATED OSTEONECROSIS OF THE JAW (BRONJ): PATHOPHYSIOLOGY, RISK FACTORS, AND CLINICAL MANAGEMENT - Biriba Filho, Alexandre Cesar (Revista Sistemática, 2023)
Bisphosphonate-related osteonecrosis of the jaw (BRONJ) is a rare but severe complication associated with the long-term use of bisphosphonates, particularly in the treatment of osteoporosis and cancer-related bone metastases. The pathogenesis of BRONJ is multifactorial, involving the inhibition of osteoclast activity, which impairs bone remodeling and leads to the accumulation of dead bone tissue. The condition is further complicated by the presence of microbial biofilms in the affected area, which play a critical role in the persistence of infection and hinder bone regeneration. Risk factors for BRONJ include prolonged bisphosphonate therapy, invasive dental procedures, pre-existing periodontal disease, and certain patient characteristics, such as advanced age or comorbidities. This article reviews current research on the mechanisms underlying BRONJ, with a particular focus on microbial biofilm formation and its implications for treatment. Studies suggest that addressing biofilm-related infection through novel antimicrobial strategies, such as bone-targeted antibiotics or topical minocycline, can be a promising approach for managing BRONJ. Additionally, advancements in pharmacokinetic modeling have enabled clinicians to assess individual patient risk based on drug dosage and duration, thus providing more personalized management strategies for bisphosphonate therapy. The article also emphasizes the importance of early identification and intervention to prevent the progression of BRONJ and reduce its impact on patients’ quality of life. While significant progress has been made in understanding the pathophysiology of BRONJ, further research is needed to optimize therapeutic approaches, refine predictive models, and explore innovative treatment options. The development of targeted antimicrobial therapies, personalized treatment regimens, and improved clinical protocols will be essential for reducing the incidence and severity of BRONJ, ultimately enhancing patient outcomes and minimizing the long-term complications associated with bisphosphonate use.